Generalized Optimal EEG Channels Selection for Motor Imagery Brain-Computer Interface - Lee, Hsiang-Chen; Lee, Ching-Hung (IEEE sensors journal, 2023)
Brain-computer interfaces (BCI) enable people to communicate with external instruments through brain activity recorded by electroencephalography (EEG). BCI based on motor imagery (MI) can distinguish activation of specific brain regions by decoding EEG signals and then applying them to different situations. Because the activation regions of the brain are specific, using all EEG channels for classification is redundant and may lead to feature confusion and inconvenience for users when applying EEG. Current EEG channel selection methods focus primarily on a single subject and require the data from the subject to generate the chosen channel, which is inconvenient on the application side to determine suitable channels for new subjects. Therefore, this study introduces a novel method for generalized EEG channel selection. Two datasets are used: the BCI competition IV 2a dataset for generating generalized EEG channels and the OpenBMI dataset for validation by numerous subjects. First, the signals from each channel are fed into EEG-Net for classification and ranked by loss to generate optimal EEG channels. Then, the methods of ranking and non-dominated sorting genetic algorithm (NSGA)-II are used to find different combinations of optimal potential differences. Finally, the generalized EEG channels are generated and validated by EEG-Net again. The validation results show that 88.5% of the subjects can be well-classified in one session, including MI-illiteracy, defined by the dataset. The average accuracy is 77.7% and 79.26% in Sessions 1 and 2, using the average channel number around 5, instead of channels from the motor cortex region or all placed EEG channels.